EXPLORING JACKFRUIT FLOUR POLYPHENOLS AS PROMISING SGLT-2 INHIBITORS FOR HYPERGLYCEMIA MANAGEMENT - PATIL, SHASHANK M.; G., MANU; M., RAMYA C.; S., RAJASHEKHARA; DESAI, SUDHANVA M.; PARAMESWARAN, SARAVANAN; RAMU, RAMITH (International Journal of Applied Pharmaceutics, 2025)
Objective: This study explored the potential of dietary polyphenols from whole green jackfruit flour as natural Sodium-Glucose Co-Transporter-2 (SGLT-2) inhibitors for managing hyperglycemia in diabetes mellitus. Methods: Advanced bio-computational techniques, including molecular docking, Molecular Dynamics (MD) simulations, and binding free energy calculations, were employed to identify and assess polyphenols from jackfruit flour. Caffeic and syringic acids were highlighted for their strong binding affinities to the SGLT-2 receptor. Additionally, a ligand-based pharmacophore model was developed using caffeic acid as a reference to screen for new lead compounds in commercial and natural product databases. Results: The study found that caffeic acid and syringic acid exhibited stronger binding affinities and more stable interaction profiles with the SGLT-2 receptor than the standard drug empagliflozin. MD simulations demonstrated that these compounds provided greater stability in the binding site, indicating their potential efficacy as SGLT-2 inhibitors. The pharmacophore screening further supported these findings, identifying both compounds as promising lead candidates. Among the 14 dietary polyphenols obtained from High-Performance Liquid Chromatography (HPLC), a molecular docking study suggested that caffeic acid (binding affinity:-9.0 kcal/mol) and syringic acid (binding affinity:-9.1 kcal/mol) exhibited stronger binding affinities and more stable interaction profiles with the SGLT-2 receptor compared to the standard drug empagliflozin (binding affinity:-10.4 kcal/mol). Further, molecular dynamics simulations demonstrated that these compounds provided greater stability in the binding site, indicating their potential efficacy as SGLT-2 inhibitors through Root mean Square Deviation (RMSD), Root mean Square Fluctuation (RMSF), Radius of Gyration (Rg), Solvent Accessible Surface Area (SASA), and ligand hydrogen bonds. The pharmacophore screening further supported these findings, identifying both compounds as promising lead candidates. Conclusion: This study is the first to identify caffeic acid and syringic acid from whole green jackfruit flour as effective SGLT-2 inhibitors. These natural compounds show significant potential as novel agents for managing hyperglycemia and diabetes mellitus. The findings support further exploration of plant-derived therapies in diabetes treatment.